Telaah Tafsir Surat Al-Imran Ayat 92 dalam Kajian Wakaf Uang Sebagai Instrumen Penguat Filantropi Ekonomi Islam - Huzni Farhany; Nina Nurkomalasari (Masoem University, 2022)
Waqf is a form of surrender of assets that we can fully return to the Giver of Property, namely Allah SWT by distributing it to people in need either for the sake of worship or for the welfare of the people. The wealth given is the best treasure we have. Philanthropy is defined as an activity of giving or in Islam commonly called ta'awun, because one of the obligations of a Muslim individual is to help others who are in need, with all the things he has, both material and embodied in an act. In Islam, there are many types of philanthropic activities, as we are discussing now, namely waqf, and others such as infaq, alms, and zakat. All of these activities become instruments in increasing philanthropy as a manifestation of prosperity and economic equity. This article discusses the utilization of cash waqf to achieve economic equality for the Indonesian people. Through a library research study with a descriptive-analytical approach, it can be concluded that the utilization of cash waqf aims to achieve economic equity in various sectors, ranging from the micro business sector, Islamic capital market to the education sector. In Indonesia, the distribution of cash waqf has begun to grow. Based on data from the Indonesian Waqf Agency (BWI), the potential for Indonesian cash waqf reaches 180 trillion per year.